Cellular signals converge at the NOX2-SHP-2 axis to induce reductive carboxylation in cancer cells. Issue 7 (21st July 2022) - Zhang, Rukang; Chen, Dong; Fan, Hao; Wu, Rong; Tu, Jiayi; Zhang, Freya Q.; Wang, Mei; Zheng, Hong; Qu, Cheng-Kui; Elf, Shannon E.; Faubert, Brandon; He, Yu-Ying; et al.
Summary: Environmental stresses, including hypoxia or detachment for anchorage independence, or attenuation of mitochondrial respiration through inhibition of electron transport chain induce reductive carboxylation in cells with an enhanced fraction of citrate arising through reductive metabolism of glutamine. This metabolic process contributes to redox homeostasis and sustains biosynthesis of lipids. Reductive carboxylation is often dependent on cytosolic isocitrate dehydrogenase 1 (IDH1). However, whether diverse cellular signals induce reductive carboxylation differentially or through a common signaling converging node remains unclear. We found that induction of reductive carboxylation commonly requires enhanced tyrosine phosphorylation and activation of IDH1, which, surprisingly, is achieved by attenuation of a cytosolic protein tyrosine phosphatase, Src homology region 2 domain-containing phosphatase-2 (SHP-2). Mechanistically, diverse signals induce reductive carboxylation by converging at upregulation of NADPH oxidase 2, leading to elevated cytosolic reactive oxygen species that consequently inhibit SHP-2. Together, our work elucidates the signaling basis underlying reductive carboxylation in cancer cells. Graphical abstract: Highlights: Tyrosine phosphorylation of IDH1 is commonly required for reductive carboxylation Reductive carboxylation attenuates SHP-2 to activate IDH1 Reductive carboxylation elevates cytosolic ROS to inhibit SHP-2 Diverse signals converge at the NOX2-SHP-2 axis to induce reductive carboxylation Abstract : The signaling basis underlying induction of reductive carboxylation remains unclear. Zhang et al. report that diverse signals converge at the NOX2-SHP-2 axis, leading to enhanced tyrosine phosphorylation and activation of IDH1 that is commonly required for induction of efficient reductive carboxylation.